Long-term productivity and sustainability of crop-livestock systems through integrated soil fertility management - Mukalama, John; Braslow, Juliet; Sommer, Rolf (2015)
Productivity in Crop-Livestock Systems can be maximized using Integrated Soil Fertility Management (ISFM). ISFM combines (i) improved germplasm (ii) mineral fertilizer application (iii) organic matter management and (v) adapted agronomy. CIAT established a long-term trial in Western Kenya in the village of Murumba Yiro in 2003 to assess ISFM technologies.